2016
DOI: 10.4236/ojl.2016.51002
|View full text |Cite
|
Sign up to set email alerts
|

Harassment Act Implementation in Higher Education Institutions

Abstract: "Effective implementation of harassment Act might be inevitable to acquiring gender equality in higher education institutions and diminishing the influence of patriarchal and conservative mind set. This study intended to explore implementation of the harassment Act (2010) in universities. Although Government of Pakistan has enforced harassment Act and Higher Education Commission (HEC) made it mandatory to implement, none of the university in the sample has implemented it. Various incidence of harassment has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…One of the key revelations from the interviews includes discrimination against women where women are not expected to freely discuss their views even in formal academic settings. Yousaf and Schmiede (2016) while addressing issue of harassment and discrimination of women in higher education echo the same view by stating that behind the glass ceiling effect on women, there is a male manager responsible for the ceiling. Like in the China context where the virtue of a woman lies in her ignorance and in Japan where a woman's knowledge is perceived as a source of unhappiness (Morley et al 2014), female academics in Pakistan are expected to remain silent even in faculty meetings because they are assumed ignorant (June, 2009).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…One of the key revelations from the interviews includes discrimination against women where women are not expected to freely discuss their views even in formal academic settings. Yousaf and Schmiede (2016) while addressing issue of harassment and discrimination of women in higher education echo the same view by stating that behind the glass ceiling effect on women, there is a male manager responsible for the ceiling. Like in the China context where the virtue of a woman lies in her ignorance and in Japan where a woman's knowledge is perceived as a source of unhappiness (Morley et al 2014), female academics in Pakistan are expected to remain silent even in faculty meetings because they are assumed ignorant (June, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies attempting to understand the "glass ceiling" on women academic careers highlight exploitation and harassment of female academics often with a male line manager as a factor (Yousaf & Schmiede 2016). The idea of a glass ceiling is often used to explain the absence of women in the senior roles of medical education (McKimm et al 2015).…”
Section: Mentoring Women In Higher Educationmentioning
confidence: 99%
“…In Pakistani literature, seven studies (Mahmood and Ahmad, 2013;Muazzam and Qayyum, 2014;Durrani and Khan, 2015;Nauman and Abbasi, 2014;Anwar, et al, 2019;Yousaf and Schmiede, 2016) had done to investigate the sexual harassments knowledge but the six of them have workplace knowledge. Only four from six studies had shown that working women had the knowledge and can define and identify sexual harassments behavior but they are not willing to do written reports on being a victim.…”
Section: Studies On the Relation Of Media Exposure/ Sexual Harassments News Exposure And Sexualmentioning
confidence: 99%
“…The assassination of Benazir Bhutto is a clear example of it (Hall, 2011). In the education sector, the Higher Education Commission (HEC) of Pakistan made it mandatory for higher educational institutes and universities to implement the HEC policy guidelines to prevent sexual harassment; but according to HEC, more than 80% of the universities of Pakistan have not implemented the law (Yousaf & Schmiede, 2016). According to Dawn News (2011), the University of Peshawar's management did not even know whether HEC policy guidelines on sexual harassment exist.…”
Section: Concept Of Sexual Harassment In the Context Of Pakistanmentioning
confidence: 99%
“…This augments the vulnerability of women to this obnoxious crime even more. Unfortunately, the incidents of sexual harassment, particularly at workplace, are multiplying with every passing day without any improvement, even though the law against these acts exists (Yousaf & Schmiede, 2016).…”
Section: Introductionmentioning
confidence: 99%